N-region etching structure, etching additive and etching polishing solution of TBC battery

By using specific etching additives and etching polishing slurries in the manufacturing of TBC cells, the etching rate is controlled, and the silicon crystal slope at the N/P region boundary is transformed into a vertical surface. This solves the problems of space waste and electric field line distortion caused by the slope in the prior art, and improves cell efficiency.

CN121126955APending Publication Date: 2025-12-12CHANGZHOU SHICHUANG ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511226664.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

In existing TBC battery manufacturing technology, it is difficult to change the {111} crystal plane slope at the junction of the N-region and P-region into a vertical plane, which leads to wasted lateral space and distortion of electric field lines, affecting battery efficiency.

Method used

By employing specific etching additives and etching polishing slurries, a directionally adsorbed electric double layer structure is formed on the silicon surface through selective inhibitors. The etching rate is controlled to form a vertical layer structure between the {111} and {100} planes, ensuring verticality. This optimizes the etching morphology at the N/P region boundary, forming a vertical morphology, shortening the lateral hole transport distance, and reducing the width of the gap region.

Benefits of technology

The vertical etching morphology at the N/P region boundary was achieved, which shortened the lateral hole transport distance, increased the effective light-receiving area, and improved battery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121126955A_ABST
    Figure CN121126955A_ABST
Patent Text Reader

Abstract

The invention discloses an N-region etching structure of a TBC battery, an etching additive and an etching polishing solution. The additive comprises the following components in percentage by mass: 0.5-1% of a selective inhibitor, 0.5-1% of a defoaming agent, 1-1.5% of a dispersing agent, 0.5-1% of a stabilizer and the balance of deionized water, wherein the selective inhibitor is a dimethyl diallyl ammonium chloride-acrylamide copolymer. The additive disclosed by the invention is applied to an N-region selective etching process of a TBC battery, and an included angle between a {111} surface and a {100} surface of a silicon crystal can be changed into a vertical morphology from a traditional 54.7-degree single inclined surface, so that the transverse transmission distance of a hole is obviously shortened, the width of a GAP region can be further reduced, and the effective light receiving area is improved, thereby obviously improving the efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of solar cell manufacturing, in particular to an N region etching structure of a TBC cell, an etching additive and an etching polishing solution. BACKGROUND

[0002] TBC technology is a new type of high-efficiency cell technology combining high-efficiency TOPCon technology and back contact (BC) technology. TBC utilizes the excellent passivation contact structure of TOPCon cells, and all electrodes are prepared on the back surface of the cell, and the front surface of the cell is free of grid lines, thereby avoiding about 3.5% of shading loss of the grid lines on the front surface of the conventional cell, and the surface is not only beautiful, but also greatly improves the photoelectric efficiency.

[0003] To achieve this, it is necessary to accurately manufacture alternating P-type regions and N-type regions on the back surface of a silicon wafer, and form corresponding electrodes (the P region corresponds to the positive electrode, and the N region corresponds to the negative electrode) on the back surface. One of the core technologies is laser patterning and selective etching. Before laser patterning and selective etching, the overall structure (from the base silicon upwards) on the back surface of the silicon wafer is generally: an N-type single crystal silicon base (matrix), an ultra-thin tunnel oxide layer (SiO X , usually 1-2 nm), a polysilicon layer (poly-Si, usually 100-200 nm), and a borosilicate glass layer (BSG). Laser patterning refers to using a laser beam of a specific wavelength (usually green or infrared) and energy density to selectively scan the BSG layer according to a preset pattern (usually a fine line or dot matrix). The BSG irradiated by the laser is modified, and the high temperature of the laser causes the BSG glass network structure in the irradiated area to change (such as partial melting, recrystallization, component segregation or formation of microcracks). The most critical change is to make the BSG in this part very easy to dissolve in the subsequent alkali etching. Then, selective alkali etching is performed, and the laser-patterned silicon wafer is immersed in an alkaline solution (such as a KOH or NaOH solution). During the etching process, the BSG in the laser-irradiated area has been modified, and the alkali solution will quickly dissolve and remove this part of the BSG until the base silicon is exposed. The BSG in the non-laser-irradiated area is not affected by the laser and is resistant to alkali etching, and the dissolution rate is very slow. Therefore, during the time when the BSG in the laser-irradiated area is quickly removed, the BSG in the non-laser-irradiated area and the underlying silicon are hardly affected or only slightly etched. The area covered by the remaining BSG is the future P-type region (underlying N-type base silicon).

[0004] During selective etching, the N-region silicon is continuously "deepened," while the P-region retains its original height, resulting in a significant height difference (approximately 1-3 micrometers) at the P / N region boundary. When the N-region is etched down to the substrate silicon, a clean and smooth polished finish is achieved. However, a distinct {111} crystal plane bevel is exposed at the P / N region boundary. This is an inevitable result of the anisotropic etching nature of single-crystal silicon and the differences in its stacked structure. Anisotropic etching is the most significant and important characteristic of alkaline etching. Silicon atoms with different crystal orientations have different bonding densities and dangling bonds, leading to huge differences in etching rates. The {111} crystal plane has the slowest etching rate, typically tens or even hundreds of times slower than other crystal planes. This is the basis for forming specific geometric structures (such as V-grooves, cantilever beams, films, pyramid structures, etc.).

[0005] The {111} ramp (54.7°) at the P / N region boundary occupies additional lateral space, requiring an increase in the effective gap width to accommodate it and compressing the effective electrode area. Furthermore, the electric field lines in the P / N region are distorted at the ramp, increasing the risk of lateral carrier recombination. If the ramp could be replaced with a vertical plane, it would save lateral space, narrow the gap width, increase the electrode area, and improve current density. Additionally, a more vertical electric field distribution would suppress lateral leakage. However, under current technological conditions, a vertical plane is difficult to achieve, and mass production faces significant challenges. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide an N-region etching structure, etching additive, and etching polishing slurry for a TBC battery. The etching additive of the present invention, when applied to the N-region etching of a TBC battery, transforms the etching morphology at the N / P region boundary from an inclined plane (54.7° angle) formed by the {111} and {100} planes of the silicon crystal to a vertical morphology. This significantly shortens the lateral hole transport distance, further reduces the width of the gap region, increases the effective light-receiving area, and thus significantly improves efficiency.

[0007] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution: This invention provides an N-region etching structure for a TBC battery, wherein the N / P region boundary has a vertical etching morphology, which includes an adjacent upper etching segment and a lower etching segment; the sidewall length of the upper etching segment is H, and its angle α with the horizontal direction satisfies: 80°≤a≤90°; the sidewall length of the lower etching segment is L, and its angle b with the horizontal direction satisfies: 50°≤b≤60°; the ratio of the sidewall length H of the upper etching segment to the sidewall length L of the lower etching segment satisfies: 1≤H / L≤2.

[0008] Another aspect of the present invention provides an N-region etching additive for TBC batteries, comprising the following components by mass percentage: 0.5-1% selective inhibitor, 0.5-1% defoamer, 1-1.5% dispersant, 0.5-1% stabilizer, and the balance being deionized water; wherein the selective inhibitor is a cationic polymer.

[0009] Preferably, the defoaming agent is selected from at least one of polysaccharide defoaming agents, hydrolyzed cellulose defoaming agents, and high molecular weight polyether dispersants.

[0010] Preferably, the selective inhibitor is a dimethyl diallyl ammonium chloride-acrylamide copolymer.

[0011] Preferably, the dispersant is selected from at least one of polyether dispersants, cationic polymer dispersants, and bio-based dispersants.

[0012] Preferably, the stabilizer is a 45-48% NaOH alkaline solution used to adjust the pH.

[0013] The present invention also provides an N-region etching and polishing solution for a TBC battery, comprising the additives and alkaline solution described above.

[0014] Preferably, the alkaline solution is a sodium hydroxide or potassium hydroxide solution.

[0015] Furthermore, the etching and polishing fluid is composed of pure water, additives, and alkaline substances; the mass ratio of pure water, additives, and alkaline substances is 100:0.5~2.0:1.0~5.0.

[0016] Furthermore, the polishing and etching temperature is 60-85℃, and the time is 100s-500s.

[0017] The technical effects of this invention are as follows: The additive proposed in this invention contains a specific selective adsorption inhibitor (dimethyldiallylammonium chloride-acrylamide copolymer). This polymer forms a directional adsorption double layer structure on a negatively charged silicon surface, with significant differences in adsorption strength at different sites and on different crystal planes. On the {111} plane, due to the dense arrangement of silicon atoms, the adsorption groups can only form single-point adsorption, while on the {100} plane, multi-point anchoring can be formed, resulting in a steric hindrance effect. Due to the difference in surface atomic arrangement between the {111} and {100} planes, the inhibitor molecules exhibit strong adsorption on the {100} plane due to the higher coordination ability of silicon atoms, forming a dense steric hindrance layer that significantly affects OH- diffusion, thereby effectively controlling the etching rate; while on the {111} plane, only a weak adsorption layer is formed, resulting in a low etching inhibition rate. By controlling the diffusion rate of OH⁻ in the adsorption layer, the {111} plane is etched relatively faster, no longer as a simple {111} crystal plane slope, but forming a layered structure of vertical and sloped planes: the upper layer near the surface is nearly vertical (tilt angle > 80°), while the lower layer retains the {111} crystal plane slope. With greater etching depth, due to the selective adsorption inhibitor forming a diffusion boundary layer on the silicon surface, the proportion of the {111} crystal plane slope is smaller, and the overall structure is closer to a vertical plane.

[0018] Defoaming agents reduce gas-liquid interfacial tension, accelerating the escape of etching byproduct hydrogen and preventing bubbles from adsorbing onto the silicon wafer surface; dispersants and selective adsorption inhibitors form a stable complex through ionic dipole interactions, enhancing their thermal stability in strongly alkaline environments and preventing decomposition caused by strong alkali and high-temperature conditions; stabilizers (sodium hydroxide) provide a stable pH environment for the long-term storage of additives, preventing the components in the additives from becoming ineffective.

[0019] The additive of the present invention, when applied to a selective etching process, can change the etching morphology at the N / P region boundary from the inclined plane (angle 54.7°) formed by the {111} plane and {100} plane of the silicon crystal to a vertical morphology, thereby significantly shortening the lateral transport distance of holes, further reducing the width of the GAP region, increasing the effective light-receiving area, and thus significantly improving efficiency. Attached Figure Description

[0020] Figure 1 This is a polishing effect diagram of the TBC sample from Example 1.

[0021] Figure 2 This is a polishing effect diagram of the TBC sample from Example 2.

[0022] Figure 3 This is a polishing effect image of the TBC sample in Comparative Example 1.

[0023] Figure 4 This is a polishing effect image of the TBC sample in Comparative Example 2. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] This invention provides an N-region etching additive for TBC batteries, comprising the following components by mass percentage: 0.5-1% selective inhibitor, 0.5-1% defoamer, 1-1.5% dispersant, 0.5-1% stabilizer, and the balance being deionized water; wherein the selective inhibitor is a dimethyl diallyl ammonium chloride-acrylamide copolymer.

[0026] Specific selective adsorption inhibitors (such as dimethyl diallyl ammonium chloride-acrylamide copolymer) can form a directional adsorption double layer structure on negatively charged silicon surfaces, with significant differences in adsorption strength at different sites and on different crystal planes. On the {111} plane, due to the dense arrangement of silicon atoms, adsorption groups can only form single-point adsorption, while on the {100} plane, multi-point anchoring can be formed, resulting in a steric hindrance effect. Thus, due to the difference in surface atomic arrangement between the {111} and {100} planes, inhibitor molecules exhibit strong adsorption on the {100} plane due to the higher coordination ability of silicon atoms, forming a dense steric hindrance layer that significantly affects OH⁻ diffusion, thereby effectively controlling the etching rate; while on the {111} plane, only a weak adsorption layer is formed, resulting in a low etching inhibition rate. By controlling the diffusion rate of OH⁻ in the adsorption layer, the {111} plane is etched relatively faster, no longer as a simple {111} crystal plane slope, but forming a layered structure with an increasing tilt angle from the surface downwards: the upper layer near the surface is nearly vertical (tilt angle > 80°), while the lower layer retains the {111} crystal plane slope. With greater etching depth, due to the selective adsorption inhibitor forming a diffusion boundary layer on the silicon surface, the proportion of the {111} crystal plane slope decreases, and the overall structure becomes closer to a vertical plane.

[0027] The defoaming agent is selected from at least one of polysaccharide defoaming agents, hydrolyzed cellulose defoaming agents, and polymeric polyether dispersants. Preferably, the defoaming agent is at least one of hydrolyzed cellulose defoaming agents or polysaccharide defoaming agents. The defoaming agent reduces the gas-liquid interfacial tension, accelerates the escape of etching byproduct hydrogen gas, and prevents bubbles from adsorbing onto the silicon wafer surface.

[0028] The dispersant is selected from at least one of polyether dispersants, cationic polymer dispersants, and bio-based dispersants. More specifically, polyethylene glycol 400 is preferred as the dispersant. The dispersant and the selective adsorption inhibitor form a stable complex through ionic dipole interaction, enhancing its thermal stability in strongly alkaline environments and preventing decomposition caused by strong alkaline and high-temperature conditions.

[0029] The stabilizer is preferably a 45-48% NaOH alkaline solution. The stabilizer (sodium hydroxide) provides a stable pH environment for the long-term storage of the additive, preventing the components in the additive from becoming ineffective.

[0030] The present invention also provides an N-region etching and polishing solution for a TBC battery, comprising the additives and alkaline solution described above.

[0031] Preferably, the alkaline solution is a sodium hydroxide or potassium hydroxide solution.

[0032] The etching and polishing slurry is composed of pure water, additives, and alkaline substances; the mass ratio of pure water, additives, and alkaline substances is 100:0.5~2.0:1.0~5.0.

[0033] The polishing and etching temperature is 60-85℃, and the time is 100s-500s.

[0034] Using the etching and polishing slurry described above, an N-region etched structure of a TBC battery with a vertical etched morphology can be obtained. This vertical etched morphology includes an adjacent upper etched section and a lower etched section. The sidewall length of the upper etched section is H, and its angle α with the horizontal direction satisfies: 80°≤a≤90°. The sidewall length of the lower etched section is L, and its angle b with the horizontal direction satisfies: 50°≤b≤60°. The ratio of the sidewall length H of the upper etched section to the sidewall length L of the lower etched section satisfies: 1≤H / L≤2.

[0035] The present invention will be further described below through specific embodiments. Example 1

[0036] Formulating additives The N-region vertical etching additive for the TBC battery in Example 1 comprises the following components by mass percentage: 0.5% selective inhibitor (dimethyl diallyl ammonium chloride-acrylamide copolymer), 0.5% defoamer (hydroxyethyl cellulose), 1% dispersant (polyethylene glycol 400), 0.5% stabilizer (48% sodium hydroxide solution), and 97.5% deionized water. The additive is obtained by uniformly mixing the above components.

[0037] Preparation of etching and polishing fluid The additive obtained above was added to a 2% potassium hydroxide aqueous solution and mixed evenly to prepare an etching and polishing solution; in the etching and polishing solution, the ratio of additive: potassium hydroxide: water = 1:2:100.

[0038] Selective etching process: The TBC sample, after optical patterning, is immersed in a polishing solution for back-side polishing. The reaction temperature is 75℃, the reaction time is 200s, and the etching depth is approximately 1μm. The polishing effect is as follows:Figure 1 As shown. By Figure 1 It can be seen that the N-region etching structure of the TBC battery sample has a vertical etching morphology; the sidewall length of the upper etching section in this vertical etching morphology is 0.5 μm, and its angle α with the horizontal direction is 89°; the sidewall length of the lower etching section is 0.3 μm, and its angle b with the horizontal direction is 53°; the ratio of the sidewall length of the upper etching section to the sidewall length of the lower etching section is 1.5. Example 2

[0039] Formulating additives The N-region vertical etching additive for the TBC battery in Example 2 comprises the following components by mass percentage: 1% selective inhibitor (dimethyl diallyl ammonium chloride-acrylamide copolymer), 0.8% defoamer (hydroxyethyl cellulose), 1.5% dispersant (polyethylene glycol 400), 0.5% stabilizer (48% sodium hydroxide solution), and 96.2% deionized water. The additive is obtained by mixing the above components thoroughly.

[0040] Preparation of etching and polishing fluid The additive obtained above was added to a 2% potassium hydroxide aqueous solution and mixed evenly to prepare an etching and polishing solution; in the etching and polishing solution, the ratio of additive: potassium hydroxide: water = 2:5:100.

[0041] Selective etching process: The TBC sample, after optical patterning, is immersed in a polishing solution for back-side polishing. The reaction temperature is 70℃, the reaction time is 400s, and the etching depth is approximately 3μm. The polishing effect is as follows: Figure 2 As shown. By Figure 2 It can be seen that the N-region etching structure of the TBC battery sample has a vertical etching morphology; the sidewall length of the upper etching section in this vertical etching morphology is 2.4 μm, and its angle α with the horizontal direction is 85°; the sidewall length of the lower etching section is 1.2 μm, and its angle b with the horizontal direction is 50°; the ratio of the sidewall length of the upper etching section to the sidewall length of the lower etching section is 2.

[0042] Comparative Example 1 Alkali polishing additive (model PS42V19, provided by Changzhou Shichuang Energy Co., Ltd.) was added to a 2% potassium hydroxide aqueous solution and mixed evenly to prepare a polishing solution; wherein the mass ratio of the conventional alkaline polishing additive to the potassium hydroxide aqueous solution was 1:100.

[0043] The TBC sample, after optical patterning, was immersed in a polishing solution for back-side polishing. The reaction temperature was 75℃, the reaction time was 200s, and the etching depth was approximately 1μm. The polishing effect is as follows: Figure 3 As shown.

[0044] Comparative Example 2 Alkali polishing additive (model PS42V19, provided by Changzhou Shichuang Energy Co., Ltd.) was added to a 2% potassium hydroxide aqueous solution and mixed evenly to prepare a polishing solution; wherein the mass ratio of the conventional alkaline polishing additive to the potassium hydroxide aqueous solution was 1:100.

[0045] The TBC sample, after optical patterning, was immersed in a polishing solution for back-side polishing. The reaction temperature was 75℃, the reaction time was 400s, and the etching depth was approximately 3μm. The polishing effect is as follows: Figure 4 As shown.

[0046] As can be seen from the comparison of the embodiments and comparative examples, the additives of the embodiments of the present invention, when applied to the selective etching process, can change the angle between the {111} plane and the {100} plane of the silicon crystal from the traditional single inclined plane to a near-vertical shape, thereby significantly shortening the lateral transmission distance of holes, further reducing the width of the GAP area, increasing the effective light-receiving area, and thus significantly improving efficiency.

[0047] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0048] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. An N-region etching structure for a TBC battery, characterized in that, After etching, the N region has a vertical etching morphology at the N / P region boundary, which includes an adjacent upper etching segment and a lower etching segment. The sidewall length of the upper etching segment is H, and its angle α with the horizontal direction satisfies: 80°≤a≤90°. The sidewall length of the lower etching segment is L, and its angle b with the horizontal direction satisfies: 50°≤b≤60°. The ratio of the sidewall length H of the upper etching segment to the sidewall length L of the lower etching segment satisfies: 1≤H / L≤2.

2. A TBC battery N-region etching additive, characterized in that, The product comprises the following components by weight percentage: 0.5-1% selective inhibitor, 0.5-1% defoamer, 1-1.5% dispersant, 0.5-1% stabilizer, and the balance being deionized water.

3. The N-region etching additive for TBC batteries according to claim 2, characterized in that, The defoaming agent is selected from at least one of polysaccharide defoaming agents, hydrolyzed cellulose defoaming agents, and high molecular weight polyether dispersants.

4. The N-region etching additive for TBC batteries according to claim 2, characterized in that, The selective inhibitor is a dimethyl diallyl ammonium chloride-acrylamide copolymer.

5. The N-region etching additive for TBC batteries according to claim 2, characterized in that, The dispersant is selected from at least one of polyether dispersants, cationic polymer dispersants, and bio-based dispersants.

6. The N-region etching additive for TBC batteries according to claim 2, characterized in that, The stabilizer is a 45-48% NaOH alkaline solution used to adjust the pH.

7. A TBC battery N-region etching and polishing slurry, characterized in that, Includes the additive and alkaline solution as described in any one of claims 2 to 6.

8. The N-region etching and polishing slurry for a TBC battery according to claim 7, characterized in that, The alkaline solution is a sodium hydroxide or potassium hydroxide solution.

9. The N-region etching and polishing slurry for a TBC battery according to claim 7, characterized in that, The etching and polishing fluid is composed of pure water, additives, and alkaline substances; the mass ratio of pure water, additives, and alkaline substances is 100:0.5~2.0:1.0~5.

0.

10. The N-region etching and polishing slurry for a TBC battery according to claim 7, characterized in that, The polishing and etching temperature is 60-85℃, and the time is 100-500s.